3D printing of CNT- and graphene-based conductive polymer nanocomposites by fused deposition modeling. (December 2017) - Gnanasekaran, K.; Heijmans, T.; van Bennekom, S.; Woldhuis, H.; Wijnia, S.; de With, G.; Friedrich, H.
Graphical abstract: Highlights: The scope of manufacturing low-cost conductive functional devices using a desktop 3D printer is discussed. Several polymer materials are analyzed and developed a new conductive polymer nanocomposites (PBT/CNT and PBT/G) for desktop 3D printing applications. The printability, esthetics and functional properties of PBT/CNT and PBT/G 3D printed composites are discussed. Strategies to 3D printing multi-materials (printing more than one material – "integrated printing") is discussed. Nozzle wear and challenges in using abrasive conductive fillers (like CNT and graphene) are discussed. Abstract: Fused deposition modeling (FDM) is limited by the availability of application specific functional materials. Here we illustrate printing of non-conventional polymer nanocomposites (CNT- and graphene-based polybutylene terephthalate (PBT)) on a commercially available desktop 3D printer leading toward printing of electrically conductive structures. The printability, electrical conductivity and mechanical stability of the polymer nanocomposites before and after 3D printing was evaluated. The results show that 3D printed PBT/CNT objects have better conductive and mechanical properties and a better performance than 3D printed PBT/graphene structures. In addition to that, printing more than one material (multi-materials) and challenges in using abrasive conductive fillers (i.e., CNT and graphene) are also discussed. Overall this study demonstrates that a commercially available desktop 3D printer can be used to fabricate low-cost functional objects.